Proceedings of the Genetic and Evolutionary Computation Conference 2016 2016
DOI: 10.1145/2908812.2908938
|View full text |Cite
|
Sign up to set email alerts
|

A Search-based Training Algorithm for Cost-aware Defect Prediction

Abstract: Research has yielded approaches to predict future defects in software artifacts based on historical information, thus assisting companies in effectively allocating limited development resources and developers in reviewing each others' code changes. Developers are unlikely to devote the same effort to inspect each software artifact predicted to contain defects, since the effort varies with the artifacts' size (cost) and the number of defects it exhibits (effectiveness). We propose to use Genetic Algorithms (GAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…Another threat regards how we assess the costeffectiveness of the models experimented. As done in previous research [9,64,2,33,49,50], we measure the inspection cost in terms of lines of code to be inspected by a reviewer. LOC has been evaluated as a valid proxy measure [2] since it is correlated with code and cognitive complexity [56].…”
Section: Threats To Validitymentioning
confidence: 99%
“…Another threat regards how we assess the costeffectiveness of the models experimented. As done in previous research [9,64,2,33,49,50], we measure the inspection cost in terms of lines of code to be inspected by a reviewer. LOC has been evaluated as a valid proxy measure [2] since it is correlated with code and cognitive complexity [56].…”
Section: Threats To Validitymentioning
confidence: 99%
“…Heterogeneous fault prediction is very promising, as it permits potentially all heterogeneous data of software projects to be used for fault predic- For the future work, we would like to use more software project data that contains both open-source and commercial proprietary projects to validate the generalization ability of our CLSUP approach. In addition, we will try to address the HFP problem with other popular techniques, such as deep learning [51] and search-based optimization methods [4,53].…”
Section: Resultsmentioning
confidence: 99%
“…They developed a multiobjective fault predictor to train logistic regression (LR) and decision trees models by using a genetic algorithm, which is a cost‐effectiveness model. Later on, Panichella et al presented to use genetic algorithms for training prediction models to maximize their cost‐effectiveness. They applied regression tree and generalized linear model to predict defects between multiple releases of six open source projects.…”
Section: Related Workmentioning
confidence: 99%
“…Panichella et al [128] presented to train defect predictors with the maximisation of their cost‐effectiveness through GAs. They employed regression tree and generalised linear model to build defect prediction models, and found that regression models trained by GAs achieve better performance than their traditional counterparts.…”
Section: Effort‐aware Context‐based Defect Prediction Studiesmentioning
confidence: 99%